The Importance of Complementarity in the Territorial Cohesion and Sustainability of Rural Areas: The Case of Cambres, a Douro Winegrowing Area, and Magueija, a Mountainous Area - Helena Pina, Ph.D., Assistant Professor (Revija za Geografijo)
Although the rural world reveals several troubling trends, such as demographic decline and stagnation/deterioration of the economic framework, there are multiple potentialities requiring urgent vitalization. Furthermore, heterogeneity predominates, a fact that becomes very clearwhen comparing the territorial setting of Cambres, a parish located in the Lamego municipality, part of the Douro winegrowing area and the area classified as World Heritage by UNESCO, with another parish set within mountainous terrain, Magueija, also located in the Lamego municipality, whose endogenous potential is completely neglected. As such, manychallenges compromise its development and conformance with one of the main strategic vectors for the region, which is territorial cohesion.